Simple Rapid Production of Calcium Acetate Lactate from Scallop Shell Waste for Agricultural Application - Sorakit Mongkol; Somkiat Seesanong; Banjong Boonchom; Nongnuch Laohavisuti; Wimonmat Boonmee; Somphob Thompho; Pesak Rungrojchaipon (International Journal of Molecular Sciences, 2025)
O, respectively. The final thermal decomposition product of all calcium compounds was calcium oxide (CaO). The CAL sample's vibrational characteristics, crystal phases, and morphologies show the binary acetate and lactate anion phases, confirming the new binary anionic calcium acetate lactate obtained. In conclusion, this research proposes an easy and low-cost technique to prepare a new valuable CAL compound using scallop shell waste as a cheap and renewable calcium source.
Keywords: Calcium Carbonate Crystallization and Inhibition; Thermal and Kinetic Analysis; Crystallization and Solubility Studies